2021
DOI: 10.1590/s0104-40362021002903296
|View full text |Cite
|
Sign up to set email alerts
|

Education during and after the pandemics

Abstract: Education in the pandemic time often received an improvised and non-realistic treatment. This is a major reason for planning now the post-pandemic period. According to the literature and document analysis, social, international and intra-national fractures, detected by current theories, were largely exposed. Besides Covid-19, other crises developed, such as impoverishment and violence. In general, the population has had losses; however, the least privileged have been subject to a greater burden. Countries cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…During the COVID-19 pandemic, families had to readjust and reconcile their children’s education and work according to their conditions experienced by social distancing. Education during the pandemic was carried out in an improvised way, causing losses in learning, and it is necessary to restore this damage by offering support to families, adolescents and educators ( 25 ) . A study carried out in Turkey showed that adolescents’ satisfaction with school life was impaired due to the uncertainties they faced during the COVID-19 pandemic associated with high levels of stress ( 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, families had to readjust and reconcile their children’s education and work according to their conditions experienced by social distancing. Education during the pandemic was carried out in an improvised way, causing losses in learning, and it is necessary to restore this damage by offering support to families, adolescents and educators ( 25 ) . A study carried out in Turkey showed that adolescents’ satisfaction with school life was impaired due to the uncertainties they faced during the COVID-19 pandemic associated with high levels of stress ( 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of coronavirus restrictions has radically changed all the forms of social interaction, including in the field of education [19]. The implementation of network learning models involving the integration of full-time and distance format becomes impossible in the context of a pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Recent major difficulties, like those resulting from the Coronavirus pandemic (ALAALI, 2022;GOMES et al, 2021;MEYER, 2022;OLIVEIRA;GOMES;BARCELLOS, 2020;THE ECONOMIST UNIT, 2020), have exposed the structural and behavioral weaknesses of HEIs around the world and especially in emerging countries. The context, characterized by deep uncertainty triggered a need for immediate changes and improvisation.…”
Section: Introductionmentioning
confidence: 99%